The Study of Life Change Unit as Stressor Agents among Tehran University of Medical Sciences Hospitals' Employees - Hossein Dargahi (Acta Medica Iranica, 2010)
Life crises as stressor agents can disrupt the best stress management regime. Different life crises have different impacts. A standard scale to rate change and its related stress impact has been developed commonly referred to as LCU (Life Change Unit) Rating. This allocates a number of Life Crisis Units or Life Change Units (LCUs) to different event and then evaluates them and takes action accordingly. This idea behind this approach of is to rundown the LCU table, totaling the LCUs for life crisis that have occurred in the previous one year. A Cross - sectional, descriptive and analytical study was conducted among 900 Tehran University of Medical Sciences (TUMS) Employees by a Holms and Rahe LCU questionnaire at 15 hospitals. The respondents were asked to determine their demographic information, list of stress symptoms which suffered from these diseases in the previous one year and finally, responded to 45 Life Change Unit as stressful life events and the value of each in "stress units" which occurred in the previous one year. The results showed that there is significant correlation between the employees LCU rating by sex, educational degree and size of hospital. Also we found that there are significant correlations between the employees stress symptoms with their LCU rating. Totally, 40% of the employees have less than 150 LCU rating (normal range) and 60% of them have 150-300 or more than 300 LCU rating (abnormal range). In conclusion most of TUMS hospitals' employees who had stress symptoms have more LCU rating. One third of these employees are not in danger of suffering the illness effect, while two third of them are in danger.